DAMPAK BANTUAN SOSIAL TUNAI (BST) COVID-19 TERHADAP KESEJAHTERAAN KELUARGA DI KABUPATEN BULELENG - Nyoman Anggaditha Mahatriandini; Putu Ayu Pramitha Purwanti (Journal Of Business, Finance, and Economics (JBFE), 2022)
For the government, the Cash Social Transfers program is a form of policy in order to help ease the burden of living for impoverished communities and affected by the Covid-19 pandemic. Cash Social Transfers is a form of social security program by the central government in the form of cash benefits to protect family welfare during the Covid-19 pandemic. Cash Social Transfers does not directly impact on increasing people's purchasing power, but the program brings benefits to them, generally short-term, namely to meet daily needs such as basic necessities, because the burden of expenses that must be borne is higher than the funds received from the Cash Social Transfers program. This research was conducted on all families in Buleleng Regency with a sample size of 100 respondents. Data collection in this study was conducted using observation, questionnaire, and interview methods. The data analysis technique used in this research is logit (logistic regression). The result of the research concludes that the variables of Cash Social Transfers and demography variables (age, education, occupation, number of family members, and gender) simultaneously affect or have positive correlation with family welfare in Buleleng Regency. Partially there is a positive correlation between Cash Social Transfers and demography variables (age, education, occupation, number of family members, and gender) to the family welfare.